2022
DOI: 10.3390/ijms23094867
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mouse Preterm Birth Induction by RU-486 on Microglial Activation and Subsequent Hypomyelination

Abstract: Preterm birth (PTB) represents 15 million births every year worldwide and is frequently associated with maternal/fetal infections and inflammation, inducing neuroinflammation. This neuroinflammation is mediated by microglial cells, which are brain-resident macrophages that release cytotoxic molecules that block oligodendrocyte differentiation, leading to hypomyelination. Some preterm survivors can face lifetime motor and/or cognitive disabilities linked to periventricular white matter injuries (PWMIs). There i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…One potential bias in assessing the effects of C-section+PBS was that the present study focused on parameters that we previously showed to be altered in the V-delivery+IL-1b group [16,[29][30][31][32]44]. Other non-studied parameters could potentially have been altered in the C-section+PBS group.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…One potential bias in assessing the effects of C-section+PBS was that the present study focused on parameters that we previously showed to be altered in the V-delivery+IL-1b group [16,[29][30][31][32]44]. Other non-studied parameters could potentially have been altered in the C-section+PBS group.…”
Section: Discussionmentioning
confidence: 93%
“…We next quantified the PDGFRα + , PDGFRα + /O4 + , and O4 + cell populations by FACS [44] at P5 (Fig. 3A-B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations